2010
DOI: 10.1371/journal.pone.0012337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Stabilizes Reconstituted Collagen Fibrils against Enzymatic Degradation by Mammalian Collagenase Matrix Metalloproteinase 8 (MMP-8)

Abstract: BackgroundCollagen, a triple-helical, self-organizing protein, is the predominant structural protein in mammals. It is found in bone, ligament, tendon, cartilage, intervertebral disc, skin, blood vessel, and cornea. We have recently postulated that fibrillar collagens (and their complementary enzymes) comprise the basis of a smart structural system which appears to support the retention of molecules in fibrils which are under tensile mechanical strain. The theory suggests that the mechanisms which drive the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
144
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(156 citation statements)
references
References 68 publications
(75 reference statements)
10
144
2
Order By: Relevance
“…Normal, physiologic loads are required to maintain tendon homeostasis and prevent excessive degradation of the extracellular matrix [25][26][27] . Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Normal, physiologic loads are required to maintain tendon homeostasis and prevent excessive degradation of the extracellular matrix [25][26][27] . Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…Nabeshima et al found that culturing nontensioned rabbit patellar tendon explants in the presence of collagenase over a period of twenty hours significantly decreased linear stiffness (p < 0.0001), elongation to failure (p < 0.002), and maximum failure force (p < 0.002) by 80% compared with explants tensioned with constant 4% strain 26 . Further, Flynn et al found that reconstituted type-I collagen micronetworks, strained between micropipettes, degraded significantly slower (p < 0.05) than unloaded controls when exposed to mammalian collagenase matrix metalloproteinase 8 27 . These experiments support the beneficial effect of mechanical load and the need for its incorporation in both clinical postoperative rehabilitation protocols and in tissue-engineering applications 27 .…”
Section: Tendon Homeostasismentioning
confidence: 99%
“…These data suggested that heterotrimeric type I collagen was more unwound than homotrimeric type I collagen, and hence, the effect of strain on further unwinding the triple helix was less pronounced in the former case (84). Conversely, strain of reconstituted type I collagen fibrils increased degradation time by MMP-8 (90). The discrepancy between the single-molecule study (84) and the fibrillar collagen study (90) may be due to effects on diffusive transport of the MMP in fibrils (84).…”
Section: Facilitation Of Collagen Catabolismmentioning
confidence: 99%
“…Conversely, strain of reconstituted type I collagen fibrils increased degradation time by MMP-8 (90). The discrepancy between the single-molecule study (84) and the fibrillar collagen study (90) may be due to effects on diffusive transport of the MMP in fibrils (84).…”
Section: Facilitation Of Collagen Catabolismmentioning
confidence: 99%
“…Biological tissues in vivo are also under tension that may interfere with the enzymatic activity. Indeed, mechanical stretch accelerates the rate of degradation of native ECM during elastase-induced digestion of lung tissue (3,4), whereas it stabilizes type I collagen against in vitro digestion by collagenases (5,6).…”
mentioning
confidence: 99%